Cyclic effect on highly thermal hybrid nano-graphene conductive ink - Salim, Mohd Azli; Mohammad Noor, Norida; Masripan, Nor Azmmi; Photong, Chonlatee; Chew, Kit Wayne; Watson, Alan (Penerbit Akademia Baru, 2025)
This research investigates the cyclic effect on highly thermal hybrid nano-graphene conductive ink. The goal is to develop and formulate a highly thermal graphene hybrid conductive ink by combining nano-graphene, silver flakes and silver acetate as conductive fillers which were mixed with chemical and organic solvents. The research evaluates the resistivity at room temperature before and after cyclic bending test in terms of electrical and mechanical properties. For this purpose, a new formulation of the conductive ink was developed using nano-graphene as the primary conductive fillers mixed with organic solvents. The mixture was sonicated and stirred to form a powder which was then dripped with 1-butanol and terpineol and mixed using a Thinky mixer to create a paste. This paste was printed onto copper substrates using a mesh stencil. The hybrid GNP paste was applied to a selected grid (3mm x 3mm) on five designated points of the substrate strip using a scraper. The samples were then cured at 250°C for 1 hour. Cyclic testing was performed using a cyclic bending test machine according to ASTM D7774-17. The formulation was characterised based on its electrical and mechanical behaviour. The resistivity of the hybrid GNP conductive ink at room temperature, without any cyclic loading, was set as the baseline. This baseline resistivity was then compared against measurements taken after 1000, 2000, 4000 and 8000 cycles. After the bending test, the reliability of the GNP hybrid formulation was assessed. Comparisons were made between the room temperature baseline and the post test samples in terms of electrical and mechanical properties. The result shows that the conductive ink exhibit initial improvements in conductivity under mechanical stress but extended cyclic bending leads to microstructural degradation with partial recovery observed after 8000 cycles indicating limited durability and potential self-healing properties. Future research should focus on enhancing the durability and self-healing properties of the hybrid conductive ink to ensure consistent performance under prolonged mechanical stress.